TRANSFORMASI DIGITAL DALAM PELAYANAN KESEHATAN KOTA BEKASI: ANALISIS PERPSEKTIF DYNAMIC CAPABILITY - Isnainy Junia Rachma (Madani Connection, 2025)
This study aims to analyze how dynamic managerial capability based on sensing, seizing, and transforming is developed in the implementation of the system for making Police Record Certificates (SKCK) at the Bekasi City Metro Police. Through a qualitative approach with case studies, this study reveals that sensing capabilities, namely the ability to detect opportunities and threats in a dynamic environment, are crucial in identifying the need to develop an online SKCK system. Seizing ability, which is the ability to take quick and appropriate action in taking advantage of opportunities, is reflected in the decision-making process and resource allocation for system implementation. Meanwhile, the ability to transform, which is the ability to change the organization to be able to adapt to change, can be seen in efforts to adapt to user feedback and technological developments. The results of this study show that the development of dynamic managerial capability based on sensing, seizing, and transforming can increase the success of the implementation of the online SKCK system, the efficiency of public services, and community satisfaction